Extraction, purification and radioiodination of Khellin as cancer theranostic agent. (December 2021) - Selim, Adli A.; Essa, Basma M.; Abdelmonem, Islam M.; Amin, Mohamed A.; Sarhan, Mona O.
Absrtract: Khellin was successfully extracted from Ammi visnaga fruits with a recovery percent of 96.15%. Next radio-iodination of Khellin was successfully achieved with a high yield. The biodistribution study of [ 131 I]iodo-khellin in tumour bearing mice revealed that khellin preferentially localization at tumour tissue. Target prediction study for [ 131 I]iodo-khellin revealed that PI3K and VEGFR are potential targets for iodo-khellin with good affinity. The results of this study potentiate [ 131 I]iodo-khellin as a good theranostic agent for tumour imaging and therapy. Graphical abstract: Image 1 Highlights: Khellin was extracted from the fresh fruits of Ammivisnaga and full characterized. Radiolabeling of Khellin with 131 I was successfully achieved with a high radiochemical yield. In-vivo study of [ 131 I]iodo-khellin in tumour bearing mice revealed its preferential localization at tumour tissue. The docking study confirmed good affinity of iodo-khellin to the predicted targets.